The Impact of City Branding and City Image on Revisit Intention Mediated Tourist Satisfaction A Case Study of Tourists - Sahal, Muhammad; Suryadi, Nanang (Profesional Muda Cendekia Publishing, 2024)
This study aims to determine the influence of City Branding and City Image on the Revisit Intention of tourists to Batu City mediated by Tourist Satisfaction. The study collected 200 samples with purposive sampling techniques. The data collection method in this study used a questionnaire with a Likert scale of 1-5. The data test in this study used SEM PLS. The results of this study show that the City Branding variable has no influence on Revisit Intention. While City Image has a positive and significant influence on Revisit Intention. In addition, this study also shows that City Branding and City Image have a positive effect on Revisit Intention with Tourist Satisfaction as a mediation variable. The benefits of this study are expected that the Batu City government can continue to improve the quality of the city's City Image in order to increase tourist return visits in Batu City. In addition, tourist satisfaction must also be a top priority for tourism business actors and the Batu City government to help create suitable City Branding and City Image in Batu City. So that tourists who come to Batu City are expected to be able to visit again in the future.